Quantitative portfolio optimization: Advanced techniques and applications - Alonso, Miquel Noguer; Camarena, Julian Antolin; Guerrero, Alberto Bueno (New Jersey John Wiley & Sons, Inc., 2025)
Quantitative Portfolio Optimization: Advanced Techniques and Applications* offers a comprehensive exploration of portfolio optimization, tracing its evolution from Harry Markowitz's Modern Portfolio Theory to contemporary techniques. The book combines foundational models like CAPM and Black-Litterman with advanced methods including Bayesian statistics, machine learning, and quantum computing.